A comparative study of the dry sliding wear of WC-10wt.%(Co+Fe+Ni) cemented carbides pressureless sintered with different Fe/Co ratios. Issue 4 (1st October 2020) - Djematene, Fares; Djerdjare, Boubekeur; Boukantar, Aniss-Rabah; Rezzoug, Amine; Abdi, Said; Daoud, Ismail; Ortiz, Angel L.
ABSTRACT: Compositional effects on the dry sliding wear resistance of micrometer-grained WC-10 wt.%(Co+Fe+Ni) cemented carbides pressureless sintered with 2 wt.% Ni but different Fe/Co ratios were investigated. Their microstructures are very similar except for the contiguity of the WC grains, which increased with increasing Fe/Co ratio. Also, these cemented carbides are all almost fully dense, but with the degree of residual porosity exhibiting a complex trend with increasing Fe/Co ratio (first decreasing and then increasing). The greatest densification was reached for an Fe/Co ratio of 1. The reverse trend was observed for the hardness, which reached HV10 =1090 kg/mm 2 for Fe/Co = 1, indicative that it is dictated essentially by the porosity. The wear resistance correlated inversely with the porosity (and thus directly with the hardness), so that the densest (and thus the hardest) of these cemented carbides (the one sintered with a Fe/Co ratio of 1) also exhibited the lowest coefficients of friction, the lowest specific wear rates, and the lowest microstructural damage. The wear mode was abrasion, with the wear mechanism being plastic deformation and especially fracture. Thus, optimization of the wear resistance of WC-(Co+Fe+Ni) cemented carbides for tribological applications is feasible by a judicious design of their binder composition.